Neuronal nuclear calcium signaling suppression of microglial reactivity is mediated by osteoprotegerin after traumatic brain injury - Fröhlich, Albrecht; Olde Heuvel, Florian; Rehman, Rida; Krishnamurthy, Sruthi Sankari; Li, Shun; Li, Zhenghui; Bayer, David; Conquest, Alison; Hertle, Anna M.; Ludolph, Albert; Huber-Lang, Markus; Boeckers, Tobias; et al. (Journal of neuroinflammation, 2022)
Traumatic brain injury (TBI) is characterized by massive changes in neuronal excitation, from acute excitotoxicity to chronic hyper- or hypoexcitability. Nuclear calcium signaling pathways are involved in translating changes in synaptic inputs and neuronal activity into discrete transcriptional programs which not only affect neuronal survival and synaptic integrity, but also the crosstalk between neurons and glial cells. Here, we report the effects of blunting neuronal nuclear calcium signals in the context of TBI.
Gesehen am 24.01.2023